Exploring contaminants as a disruptor of temperature-dependent sex determination in sea turtle hatchlings - Barraza, Arthur D.; Young, Larissa; Smith, Caitlin E.; Booth, David T.; Hof, Christine A. Madden; Finlayson, Kimberly A.; Leusch, Frederic D. L.; van de Merwe, Jason P. (Frontiers in Marine Science, 2023)
Sea turtle nesting beaches are experiencing increased sand temperatures as climate change progresses. In one major green turtle (Chelonia mydas) nesting beach in the northern Great Barrier Reef, over 99 percent of hatchlings are female. The effects of contaminants on sea turtle hatchling sex determination are not often explored. Liver samples were collected from green turtle hatchlings that were sacrificed for histological sex determination in a parallel study on the effects of sand cooling on sex ratios, and analysed for trace elements via acid digestion and organic contaminants via in vitro cytotoxicity bioassays. Chromium, antimony, barium, and cadmium have previously been demonstrated to be estrogenic, and concentrations of these elements were used to calculate three estrogenic indexes for each clutch: predicted relative estrogenic potency (PEEQA), the sum of percent trace elements above the median of all samples (TEOM), and the sum of percent estrogenic elements above the median of all samples (EstroEOM). Excluding an outlier clutch, cadmium, antimony, and EstroEOM had significant positive relationships with sex ratio deviation. Mean clutch cobalt, lead, antimony and barium, also had a significant positive relationship with clutch sex ratio. There was no relationship between in vitro cytotoxicity of liver extracts and sex ratio, however, 9% of hatchlings had organic contaminants high enough to suggest potential cellular damage. Contaminant effects on sex determination are likely to be caused by a mixture of contaminant interactions as well as temperature. Many trace elements detected in this study have also been linked to negative health effects on hatchlings in previous studies. Considering the risks of feminization due to climate change and potential contaminant effects on hatchling health and sex determination, future studies exploring contaminant effects on sea turtle hatchling sex determination are recommended.